Perbandingan antigen larut (SA) Brugia malayi dan Brugia pahangi di dalam pengembangan sistem ELISA untuk diagnosis penyakit Filaria - Noordin, Rahmah; Abdullah, Khairul Anuar; Bakar, Afifi Sheikh Abu (1999)
Brugia malayi and Brugia pahangi adult worm soluble antigens were used in digoxigenin-sandwich ELISA to detect filarial specific anti-IgG4 and antiIgG2 antibodies in different groups of filarial patients, soil-transmitted helminth infected patients and in normal individuals. Both kinds of antigens showed positive IgG4 responses with all sera of microfilaraemic patients. However, ELISA using B. pahangi antigen also showed positive ELISA readings with some sera of patients with soil-transmitted helminth infections and some sera of normal individuals. On the other hand no such cross-reactivities were demonstrated when B. malayi was used as the antigen. In the analysis of anti-filarial IgG2 antibody responses, all chronic elephantiasis sera gave positive readings in ELlS As that employed B. malayi as the antigen; and no cross-reactivity with other helminthic infections were observed. In comparison, only some sera of chronic elephantiasis patients were positive for antifilaral IgG2 antibodies when B. pahangi was used as the antigen. Furthermore, with the use of B. pahangi antigen coated plates, some sera from soil-transmitted helminth infected patients and from normal individuals also showed positive titres of antifilarial IgG2 antibodies. This study demonstrated that B. pahangi soluble adult worm antigen is not a suitable substitute for B. malayi soluble adult worm antigen in the diagnosis of brugian filariasis by ELISA.